Deterministic synthesis of Cu9S5 flakes assisted by single-layer graphene arrays. Issue 5 (16th February 2021) - Portone, A.; Bellucci, L.; Convertino, D.; Mezzadri, F.; Piccinini, G.; Giambra, M. A.; Miseikis, V.; Rossi, F.; Coletti, C.; Fabbri, F.
Abstract : The employment of 2D materials, as growth substrates or buffer layers, enables the epitaxial growth of layered materials with different crystalline symmetries with a preferential crystalline orientation and the synthesis of heterostructures with a large lattice constant mismatch. Abstract : The employment of two-dimensional materials, as growth substrates or buffer layers, enables the epitaxial growth of layered materials with different crystalline symmetries with a preferential crystalline orientation and the synthesis of heterostructures with a large lattice constant mismatch. In this work, we employ single crystalline graphene to modify the sulfurization dynamics of copper foil for the deterministic synthesis of large-area Cu9 S5 crystals. Molecular dynamics simulations using the Reax force-field are used to mimic the sulfurization process of a series of different atomistic systems specifically built to understand the role of graphene during the sulphur atom attack over the Cu(111) surface. Cu9 S5 flakes show a flat morphology with an average lateral size of hundreds of micrometers. Cu9 S5 presents a direct band-gap of 2.5 eV evaluated with light absorption and light emission spectroscopies. Electrical characterization shows that the Cu9 S5 crystals present high p-type doping with a hole mobility of 2 cm 2 V −1 s −1 .